The American agent : [compact disc, unabridged] a Maisie Dobbs novel - Winspear, Jacqueline, 1955- (Winspear, Jacqueline, 1955- Maisie Dobbs novel (Audio), 2019)
When Catherine Saxon, an American correspondent reporting on the war in Europe, is found murdered in her London digs, news of her death is concealed by British authorities. Serving as a linchpin between Scotland Yard and the Secret Service, Robert MacFarlane pays a visit to Maisie Dobbs, seeking her help. He is accompanied by an agent from the US Department of Justice, Mark Scott, the American who helped Maisie get out of Hitler's Munich in 1938. MacFarlane asks Maisie to work with Scott to uncover the truth about Saxon's death. As the Germans unleash the full terror of their blitzkrieg upon the British Isles, raining death and destruction from the skies, Maisie must balance the demands of solving this dangerous case with her need to protect Anna, the young evacuee she has grown to love and wants to adopt.